Genetically engineered bacteria-based nanocomposite synergistic HIFU for tumor therapy by changing the acoustic environment of tumor tissues - Ting Gong; Wen Zhao; Youqiang Chen; Youqian He; Jie Xiong; Yijun Xiong; Liu Yin; Yong Luo; Yi Tang (Cancer Cell International)
Abstract High-intensity focused ultrasound (HIFU) is a novel non-invasive technique with tremendous potential applications. However, ensuring effectiveness and safety of HIFU therapy remains a substantial challenge. Changing the acoustic environment of tumor tissues is an emerging way to solve this problem. In this study, we successfully constructed a bacteria-based nanocomposite, consisting genetically engineered bacteria (GVs-E.coli) and perfluorohexane/poly(lactic-co-glycolic acid) (PFH/PLGA) nanoparticles, which is denoted as GVs-E@PP NPs. We demonstrated that GVs-E@PP NPs could selectively target and proliferate in the tumor sites, and enhance the efficacy of HIFU therapy by changing the acoustic environment of tumor tissues. Specifically, they induced an increase in collagen fibers, elastic modulus, sound velocity and sound attenuation within tumor tissues, while simultaneously reducing tumor angiogenesis. These comprehensive changes facilitated the therapeutic efficacy of HIFU treatment. In summary, this approach represents an innovative therapeutic strategy to enhance HIFU synergy in tumor treatment.